Possible relationship between long-term post neutering complications in dogs and caregiver burden in the owners - Bastan, Idil (Frontiers in Veterinary Science, 2025)
Gonadectomy, commonly known as neutering, is widely used to address dog overpopulation and reduce reproductive disease risks, such as mammary cancer and pyometra. It is also advocated for behavior modification. However, neutering is associated with an increased risk of certain musculoskeletal disorders, obesity, several types of cancer, immune-mediated diseases, and cognitive dysfunction. These conditions may necessitate ongoing care and treatment, that require special care that the caregiver must provide furthermore burdens the caregiver with daily tasks, which encompasses the emotional, physical, social, and financial impact on pet owners caring for chronically ill animals. This burden can result in burnout, health issues, depression, social isolation, and financial stress. The potential benefits and risk of gonadectomy can affect the quality of life of both humans and pets. Relevant research findings should therefore be incorporated into each pet's and owner's particular situation. The purpose of this review is to address the long-term neutering risks and the potential caregiver burden that arises from these risks.